2010
DOI: 10.1186/1742-4755-7-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress as predictor of quality of life in men experiencing infertility: a cross-sectional survey

Abstract: BackgroundInfertility is associated with impairment in human life. The quality of life (QOL) construct allows measuring the impact of health conditions in a broader way. The study aimed to explore the impact of the psychological distress on QOL's dimensions in men experiencing infertility.Methods162 men were completed a socio-demographic form, SF-36, WHOQOL-BREF, Beck Anxiety Inventory and Beck Depression Inventory. Hierarchical regressions included demographic and clinic variables, and subsequently depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Especially, notable were the effects of two-week Morbidity Rate, anemia symptoms, muscular soreness and urinary system disease (Table 4). Previously studies also demonstrated that chronic diseases were associated with lower QOL [40][41][42]. Vaez et al compared health status and QOL assessments of first year university students with those of their same-age working counterparts.…”
Section: Quality Of Lifementioning
confidence: 98%
“…Especially, notable were the effects of two-week Morbidity Rate, anemia symptoms, muscular soreness and urinary system disease (Table 4). Previously studies also demonstrated that chronic diseases were associated with lower QOL [40][41][42]. Vaez et al compared health status and QOL assessments of first year university students with those of their same-age working counterparts.…”
Section: Quality Of Lifementioning
confidence: 98%
“…The scale consists of 16 questions to measure infertile patients' perceptions regarding their ability to involve in an integrative performance in the aspects of cognition, emotion, and behaviors which are associated with the infertility medical treatment. The ISE scale requires respondents to indicate respondents' degree of agreement with each item on a nine-point Likert scale ranging from strongly disagree (1) to strongly agree (9). The overall score ranges from 16 to 144, where the higher the score, the higher the ISE.…”
Section: Measurementsmentioning
confidence: 99%
“…Arthur Greil and colleagues argue that, in “advanced industrialized societies,” women often experience infertility as a “secret stigma” because many assume that they are childless by choice . Although most studies focus on infertile women, infertile men also experience anxiety, depression, and poor quality of life …”
Section: Financing Fertility Treatments May Reduce Stigma and Improvementioning
confidence: 99%
“…15 Although most studies focus on infertile women, infertile men also experience anxiety, depression, and poor quality of life. 16 While the medicalization of conditions that were previously understood as nonmedical can sometimes create problems, it can simultaneously lead to positive outcomes. For example, treating children with emotional and behavioral disturbances as sick, rather than as bad, can improve their access to helpful interventions.…”
Section: Financing Fertility Treatments May Reducementioning
confidence: 99%